Primary non-Hodgkin lymphoma in the muscle of left lower extremity: a case report and literature review - Du, Haixia; Zhang, Yongting; Zhou, Hong; Huo, Xiaoguang; Xu, Mengying; Xu, Wenzhe (Frontiers in Oncology, 2025)
Primary non-Hodgkin lymphoma (NHL) of the left lower extremity muscle is a rare extra-nodal lymphoma, accounting for less than 1% of all extra-nodal NHL cases. We report a rare case of intramuscular NHL of the left lower extremity and discuss its clinical features, diagnostic challenges, and treatment strategies with reference to the literature. The patient, an adult man, was treated for sudden swelling and pain in the left lower limb. Ultrasound examination revealed hypoechoic myometrium (hematoma considered), and ultrasound-guided puncture biopsy confirmed “primary CD5+ diffuse large B-cell lymphoma (leg type)”. The patient received six cycles of chemotherapy, and his symptoms were significantly relieved, but an early local recurrence occurred. The clinical manifestations and imaging features of primary NHL in skeletal muscle lacked specificity, and the diagnosis depended on pathology and molecular analysis. Its pathogenesis may be related to direct invasion, hematogenous metastasis, or primary muscle lesions. CD5+ diffuse large B-cell lymphoma (DLBCL) is aggressive, and Rituximab-Cyclophosphamide Hydroxydaunorubicin Vincristine Prednisone (R-CHOP) combined with radiotherapy is recommended, but prognosis is affected by age, Lactate Dehydrogenase (LDH) levels, and molecular characteristics such as TP53 mutations. Primary non-Hodgkin lymphoma in the muscle of the left lower limb is very rare. It is difficult to diagnose it by imaging examination alone. It needs to be considered comprehensively by combining various examination methods. Pathology is the gold standard for diagnosis. Radiotherapy and chemotherapy are the first choice for treatment. It is very important to formulate a reasonable treatment plan according to the results of pathology and molecular analysis.